Future of artificial intelligence for the diagnosis and treatment of retinal diseases - E.A. Katalevskaya; D.Yu. Katalevskiy; M.I. Tyurikov; I.A. Velieva; A.V. Bol’shunov (РМЖ "Клиническая офтальмология")
E.A. Katalevskaya1, D.Yu. Katalevskiy1,2, M.I. Tyurikov1,3, I.A. Velieva4, A.V. Bol’shunov4 1LLC "Digital Vision Solutions", Moscow, Russian Federation 2Russian Presidential Academy of National Economy and Public Administration (RANEPA), Moscow, Russian Federation 3Nizhny Novgorod State Technical University named after R.E. Alekseev, Nizhny Novgorod, Russian Federation 4Scientific Research Institute of Eye Diseases, Moscow, Russian Federation Artificial intelligence (AI) is a branch of informatics concerned with developing programs capable of imitating certain functions of the human mind. AI technologies are applied in different areas of medicine, including ophthalmology. Acquisition and analysis of images are critical for diagnosing and treating ophthalmic disorders, particularly retinal diseases. This paper reviews the use of AI algorithms for diagnosing and treating retinal disorders. Modern AI algorithms are trained to analyze images obtained by digital retinal photography, optical coherence tomography, and optical coherence tomography angiography. The most promising AI algorithms are those used for screening and treating chronic diseases (e.g., diabetic retinopathy, diabetic macular edema, age-related macular degeneration) to provide a personalized management strategy. Therefore, developing standards regulating AI technology application and standards providing a reliable evaluation of  safety, accuracy, and  reliability of AI-based system functioning is particularly important for healthcare. Keywords: artificial intelligence, computer vision, ophthalmic screening, diabetic retinopathy, diabetic macular edema, age-related macular degeneration. For citation: Katalevskaya E.A., Katalevskiy D.Yu., Tyurikov M.I. et al. Future of artificial intelligence for the diagnosis and treatment of retinal diseases. Russian Journal of Clinical Ophthalmology. 2022;22(1):36–43 (in Russ.). DOI: 10.32364/2311-7729-2022-22-1-36-43.